1999
DOI: 10.1007/s001250051114
|View full text |Cite
|
Sign up to set email alerts
|

Transcapillary escape rate and albuminuria in Type II diabetes. Effects of short-term treatment with low-molecular weight heparin (Short Communication)

Abstract: Type II (non-insulin-dependent) diabetic patients with abnormal urinary albumin excretion rate (UAE), even in the microalbuminuric range (UAE 20±200 mg/min), have an increased prevalence of vascular disease and risk of cardiovascular events compared with patients with normoalbuminuria (UAE < 20 mg/min) [1±5]. The association has raised the hypothesis that patients with increased albuminuria do not only have glomerular disease but also extensive vascular damage [6,7]. Increased transcapillary escape rate of alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
(36 reference statements)
2
12
0
2
Order By: Relevance
“…Both demonstrated that sulodexide was effective as a hypoalbuminuric agent. The effect of GAGs on macroalbuminuria in DM2 patients has been explored in two studies; however, tinzaparin (42) and danaparoid (21) were administered parenterally, making direct comparison difficult. The negative results obtained from both studies have raised the doubt that DM2 patients are less sensitive to GAGs than DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both demonstrated that sulodexide was effective as a hypoalbuminuric agent. The effect of GAGs on macroalbuminuria in DM2 patients has been explored in two studies; however, tinzaparin (42) and danaparoid (21) were administered parenterally, making direct comparison difficult. The negative results obtained from both studies have raised the doubt that DM2 patients are less sensitive to GAGs than DM1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in molecular weight and anti-X and anti-II activity may be indirect hallmarks of different renoprotective potency of the heparin formulation used. 18 Based upon epidemiological data, the genetic differences in the enzymes involved in the sulphation of GAG side-chains of heparan sulphate proteoglycans are of crucial importance in the pathogenesis of DN and the recent in-vitro and in-vivo studies have put light on the role of HS-GAG in the pathogenesis of DN. 19 In addition, various experimental and human studies have shown heparin to reduce proteinuria and prevent thickening of glomerular basement membrane glomerular and anionic charge in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in UAER were seen with enoxaparin but not with tinzaparin; for danaparoid, reductions occurred with Type 1 but not with Type 2 DM patients. 8,[20][21][22] Thus, the exact role of heparinoid supplementation in DKD remains unknown and these substances are not part of treatment recommendations. This study attempts to consolidate available information and evaluate their safety and efficacy in DKD patients.…”
Section: Data Extraction and Managementmentioning
confidence: 99%
“…8,13,15,18,[19][20][21][22][23] The incidence of likely study-related side effects was similar by removing one study at a time, starting with the studies that had the highest potential risk for bias. We subsequently found no significant changes in the values of the pooled log-transformed MD, indicating the quality of the studies to be satisfactory.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation